2015
DOI: 10.2522/ptj.20140090
|View full text |Cite
|
Sign up to set email alerts
|

Does Perturbation-Based Balance Training Prevent Falls? Systematic Review and Meta-Analysis of Preliminary Randomized Controlled Trials

Abstract: Perturbation-based balance training appears to reduce fall risk among older adults and individuals with Parkinson disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
184
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(195 citation statements)
references
References 40 publications
5
184
1
5
Order By: Relevance
“…The original publication did not report falls data, but prospective falls data were recorded (reported in Mansfield et al. 29). These data did not show significant reductions in falls incidence; however, the study was not powered for this outcome measure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The original publication did not report falls data, but prospective falls data were recorded (reported in Mansfield et al. 29). These data did not show significant reductions in falls incidence; however, the study was not powered for this outcome measure.…”
Section: Resultsmentioning
confidence: 99%
“…PBT), the reactive balance control of older adults could be improved, which might reduce their falls risk. One recent meta‐analysis of randomized controlled trials using PBT indeed reported a significantly lower falls incidence in PBT groups after the interventions,29 with a second meta‐analysis combining studies of PBT with voluntary stepping interventions also reporting reduced falls incidence 30. However, despite this evidence, it is important to consider whether such training is effective and feasible in clinical settings, or whether such benefits are only seen in highly controlled laboratory settings, information that is not yet explored in detail in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is common to use strengthening exercises in conjunction with exercises addressing motor control components of balance, such as seen in the widely used OTAGO exercise protocol [12]. We do have guidelines for determining types of exercise, based on an individualized evaluation [2], although there are newer interventions, such as perturbation training, that show excellent promise as well [13]. We also have some guidelines related to the frequency and duration needed for an exercise program to be effective in certain setting and with certain populations [14].…”
Section: Editorialmentioning
confidence: 99%
“…Future work should continue to investigate the effects of PBT with task-specific interventions within this population as well as its impact on standardized outcome measures. 6,[10][11][12][13] associated with fewer number of falls. Perturbation-based balance training (PBT) is defined as "a novel balance training intervention that incorporates exposure to repeated postural perturbations to evoke a rapid balance reaction, enabling the individual to improve 6 control of these reactions with practice."…”
Section: Introductionmentioning
confidence: 99%
“…While ankle and hip strategies have been found to be effective ways to maintain balance and prevent falls following perturbations, a stepping strategy, or reaction, 5 5 has also been found to be successful and even the preferred strategy. Horak, et al defined a stepping reaction as an "asymmetrical loading and unloading of the legs to move the base of 6 support under the falling center of mass" and Mansfield, et al further stated that in order to prevent falls, this motion must occur quicker than a typical voluntary movement. A protective stepping reaction is a necessary reactive balance response to prevent falls resulting from [5][6][7][8][9] postural perturbations, and therefore people with an ineffective stepping reaction are likely 6 at an increased risk for falls.…”
Section: Introductionmentioning
confidence: 99%